Using permutation function and the Bank of LFSR's in pseudo random generator keys - Ali Khalil Salih (Tikrit Journal of Pure Science, 2023)
In this paper a Bank of Linear Feedback Shift Registers (LFSR) is used to design and build a system for cryptography. This algorithm consists of 16 Linear Feedback Shift Registers. When we choose eight Shift Registers for each operation of this system, we get one byte constantly this operation.